Reduced cardiac index reserve and hypovolemia in severe falciparum malaria - Kingston, H; Ghose, A; Rungpradubvong, V; Satitthummanid, S; Herdman, M; Plewes, K; Leopold, S; Ishioka, H; Mohanty, S; Maude, R; Schultz, M; Lagrand, W; et al. (Oxford University Press, 2019)
Background: Impaired microvascular perfusion is central to the development of coma and lactic acidosis in severe falciparum malaria. Refractory hypotension is rare on admission but develops frequently in fatal cases. We assessed cardiac function and volume status in severe falciparum malaria and its prognostic significance.